2008
DOI: 10.3748/wjg.14.7086
|View full text |Cite
|
Sign up to set email alerts
|

Web-based system for training and dissemination of a magnification chromoendoscopy classification

Abstract: AIM:To evaluate the use of web-based technologies to assess the learning curve and reassess reproducibility of a simplified version of a classification for gastric magnification chromoendoscopy (MC). METHODS: As part of a multicenter trial, a hybrid approach was taken using a CD-ROM, with 20 films of MC lasting 5 s each and an "autorun" file triggering a local HTML frameset referenced to a remote questionnaire through an Internet connection. Three endoscopists were asked to prospectively and independently clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…It was reported that there was no difference in the accuracy between in-classroom and self-directed didactic training programs of NBI for diagnosis of Barrett's esophagusassociated neoplasia [26]. An Internet-based e-learning system for training in the endoscopy field has been reported, and is expected to become a promising training resource [19,20]. With the recent development of the Internet learning environment, there is no limit to the number of learners to whom it is now possible to transmit the latest knowledge combined with numerous images.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that there was no difference in the accuracy between in-classroom and self-directed didactic training programs of NBI for diagnosis of Barrett's esophagusassociated neoplasia [26]. An Internet-based e-learning system for training in the endoscopy field has been reported, and is expected to become a promising training resource [19,20]. With the recent development of the Internet learning environment, there is no limit to the number of learners to whom it is now possible to transmit the latest knowledge combined with numerous images.…”
Section: Discussionmentioning
confidence: 99%
“…We used a validated set of still pictures followed by a practice on real colonoscopies with auto-administered feedback, hypothesizing that the latter would ease the transition from still pictures to real practice and shorten the learning curve. For the initial learning steps, several training modules have been used in the literature, including classroom-type[ 8 , 18 ], computer training[ 19 ] and web-based[ 20 ] modules. All systems may have similar efficacy as it has been suggested in a recent report showing that self-learning using a computer-based program with pictures and videos is as efficient as a classroom-type teaching session for learning OD[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are almost no records of moving images when an observer wants to recheck the lesion and when endoscopists other than the observer want to diagnose the lesion. In contrast, with the widespread availability of Internet resources, learning programs with web-based videos are becoming a great tool to improve the diagnostic yield with endoscopy [22] , [23] , [24] . To our knowledge, the difference between still images and moving images has not been adequately evaluated.…”
Section: Discussionmentioning
confidence: 99%